11.5k views
0 votes
Look at my question

Look at my question-example-1
User Joya
by
6.4k points

1 Answer

3 votes

Answer:

option D


(2)/((k+2))

Step-by-step explanation:

Given in the question an expression


(4k+2)/(k^(2)-4).(k-2)/(2k+1)

Step 1

Use Algebraic Formula

a² - b² = (a-b)(a+b)

k² - 4 = k² - (2)² = (k-2)(k+2)


(4k+2)/((k-2)(k+2)).(k-2)/(2k+1)

Step 2

Cancel(k-2) from both numerator and denometor


(4k+2)/((k+2)).(1)/(2k+1)

Step 3

Use Distributive Law

a(b+c) = (ab + ac)

4k + 2 = 2(2k+1)


(2(2k+1))/((k+2)).(1)/(2k+1)

Step 4

Cancel(2k+1) from both numerator and denometor


(2)/((k+2)).(1)/(1)

Step 5

Simplified form is


(2)/((k+2))

User Alexander Morland
by
5.3k points